Detection of cancer stem cell markers in sarcomas - Veselska, R; Skoda, J; Neradil, J (Klinicka onkologie, 2012)
The identification of cancer stem cell markers represents one of the very relevant research topics because cancer stem cells play important roles in tumour initiation and progression, as well as during metastasis formation and in relapse of the disease. This article summarises recent knowledge on well-known and putative cancer stem cell markers in various types of bone and soft-tissue sarcomas. Special attention is paid to the detection of CD133, ABC transporters, nestin and aldehyde dehydrogenase that have been intensively studied both in tumour tissues and in sarcoma cell lines during the past few years. Finally, an overview is given of the possible CSC phenotypes provided by functional assays of tumourigenicity.
Keywords: Neoplastic Stem Cells; ATP-Binding Cassette Transporters; Peptides; nestin; aldehyddehydrogenasa; proteiny nervové tkáně; nádorové kmenové buňky; Antigens, CD; nádorové biomarkery; CD antigeny; Humans; Glycoproteins; Biomarkers, Tumor; proteiny intermediálních filament; ABC transportéry; sarkom; Aldehyde Dehydrogenase; antigen AC133; Intermediate Filament Proteins; Nestin; glykoproteiny; lidé; AC133 Antigen; peptidy; Sarcoma; Nerve Tissue Proteins